Dose modifications in adjuvant chemotherapy for solid organ malignancies: A systematic review of clinical trials. Issue 3 (2nd March 2018) - Prasanna, Thiru; Beith, Jane; Kao, Steven; Boyer, Michael; McNeil, Catriona M.
Abstract: Toxicities of systemic cancer therapies are often less frequently observed in clinical trials than in clinical practice, due to the careful selection of patients with fewer comorbidities. Although guidelines exist for the estimation of chemotherapy dose, clinical factors like age, comorbid illness and extremes of body habitus are not considered in the method of dose calculation, which can result in significant toxicity. We reviewed the referenced clinical trials from which the evidence‐based curative‐intent cancer treatment protocols were developed for EVIQ, which is an Australian government, online resource. This review shows that a significant proportion of patients in curative‐intent clinical trials experience toxicities that result in dose modifications—dose reduction, dose delays or missed doses—despite strict selection criteria and intense monitoring. Thus, even in ideal, clinical‐trial settings chemotherapy dose calculation remains imprecise and subject to adjustment as clinically appropriate. In real‐world clinical practice, dose alterations or modifications in response to toxicities need to be thoroughly discussed and implemented with clear understanding of the patient with appropriate documentation. This review may be used as a reference in these situations to elaborate the extent of toxicities seen in clinical trials with optimal settings.